COMPREHENSIVE ASSESSMENT OF THE MELIORATIVE STATE OF IRRIGATED LANDS IN KHOREZM REGION UNDER CLIMATE CHANGE CONDITIONS - Tajiyev, Qudrat Qadirberganovich (SCIENCE and SOCIETY, 2026)
The study analyzes the relationship between climate change, groundwater, and soil salinization in the irrigated lands of Khorezm region. Using the newly developed Meliorative Condition Integration Index (MCII), it was found that 38% of the region’s territory is at high risk, with this figure potentially reaching 47–55% by 2050.